A global quantitative survey of hemostatic assessment in postpartum hemorrhage and experience with associated bleeding disorders - James, Andra H (Int J Womens Health, 2017)
PURPOSE: Coagulopathy may be a serious complicating or contributing factor to postpartum hemorrhage (PPH), and should be promptly recognized to ensure proper bleeding management. This study aims to evaluate the approaches of obstetrician-gynecologists worldwide towards assessing massive PPH caused by underlying bleeding disorders. METHODS: A quantitative survey was completed by 302 obstetrician-gynecologists from 6 countries (the UK, France, Germany, Italy, Spain, and Japan). The survey included questions on the use of hematologic laboratory studies, interpretation of results, laboratory’s role in coagulation assessments, and experience with bleeding disorders. RESULTS: Overall, the most common definitions of “massive” PPH were >2,000 mL (39%) and >1,500 mL (34%) blood loss. The most common criteria for rechecking a “stat” complete blood count and for performing coagulation studies were a drop in blood pressure (73%) and ongoing visible bleeding (78%), respectively. Laboratory coagulation (prothrombin time/activated partial thromboplastin time [PT/aPTT]) and factor VIII/IX assays were performed on-site more often than were mixing studies (laboratory coagulation studies, 93%; factor VIII/IX assays, 63%; mixing studies, 22%). Most commonly consulted sources of additional information were colleagues within one’s own specialty (68%) and other specialists (67%). Most respondents had consulted with a hematologist (78%; least, Germany [56%]; greatest, UK [98%]). The most common reason for not consulting was hematologist unavailability (44%). The most commonly reported thresholds for concern with PT and aPTT were 13 to 20 seconds (36%) and 30 to 45 seconds (50%), respectively. Most respondents reported having discovered an underlying bleeding disorder (58%; least, Japan [35%]; greatest, Spain [74%]). CONCLUSION: Global survey results highlight similarities and differences between countries in how PPH is assessed and varying levels of obstetrician-gynecologist experience with identification of underlying bleeding disorders and engagement of hematology consultants. Opportunities to improve patient management of PPH associated with bleeding disorders include greater familiarity with interpreting PT/aPTT test results and identification of and consistent consultation with hematologists with relevant expertise.